Photobiological Interactions of Blue Light and Photosynthetic Photon Flux: Effects of Monochromatic and Broad‐Spectrum Light Sources. (18th January 2014) - Cope, Kevin R.; Snowden, M. Chase; Bugbee, Bruce
Abstract Photosynthesis (Pn) and photomorphogenesis (Pm) are affected by light quality, light intensity and photoperiod. Although blue light (BL) is necessary for normal development, it is less efficient in driving Pn than other wavelengths of photosynthetically active radiation. The effects of BL on Pm are highly species dependent. Here we report the interacting effects of BL and photosynthetic photon flux (PPF) on growth and development of lettuce, radish and pepper. We used light‐emitting diode (LED) arrays to provide BL fractions from 11% to 28% under broad‐spectrum white LEDs, and from 0.3% to 92% under monochromatic LEDs. All treatments were replicated three times at each of two PPFs (200 and 500 μmol m−2 s−1). Other than light quality, environmental conditions were uniformly maintained across chambers. Regardless of PPF, BL was necessary to prevent shade‐avoidance responses in radish and lettuce. For lettuce and radish, increasing BL reduced stem length, and for both species, there were significant interactions of BL with PPF for leaf expansion. Increasing BL reduced petiole length in radish and flower number in pepper. BL minimally affected pepper growth and other developmental parameters. Pepper seedlings were more photobiologically sensitive than older plants. Surprisingly, there were few interactions between monochromatic and broad‐spectrum light sources.